2019
DOI: 10.1186/s12885-019-6296-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cancer incidence, stage at diagnosis and outcomes of First Nations and all other Manitobans: a retrospective analysis

Abstract: BackgroundGlobally, epidemiological evidence suggests cancer incidence and outcomes among Indigenous peoples are a growing concern. Although historically cancer among First Nations (FN) peoples in Canada was relatively unknown, recent epidemiological evidence reveals a widening of cancer related disparities. However evidence at the population level is limited. The aim of this study was to explore cancer incidence, stage at diagnosis, and outcomes among status FN peoples in comparison with all other Manitobans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Cancer stage at diagnosis, an important predictor of disease course and treatment options and indicator of the quality of and access to screening and early detection efforts (CPAC, 2015;Decker et al, 2016), is also concerning. FN Peoples are more likely to be diagnosed with 'late-stage' cancers than non-FN (Decker et al, 2016;Horrill et al 2019b;Sheppard et al, 2010), which can result in limited, more invasive, or costly treatment. Cancer survival is significantly poorer among FN Peoples compared to non-FN (Erickson et al, 2015;McGahan et al, 2017;Nishri et al, 2015;Withrow et al, 2017).…”
Section: Cancer Disparities Among First Nations Peoplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer stage at diagnosis, an important predictor of disease course and treatment options and indicator of the quality of and access to screening and early detection efforts (CPAC, 2015;Decker et al, 2016), is also concerning. FN Peoples are more likely to be diagnosed with 'late-stage' cancers than non-FN (Decker et al, 2016;Horrill et al 2019b;Sheppard et al, 2010), which can result in limited, more invasive, or costly treatment. Cancer survival is significantly poorer among FN Peoples compared to non-FN (Erickson et al, 2015;McGahan et al, 2017;Nishri et al, 2015;Withrow et al, 2017).…”
Section: Cancer Disparities Among First Nations Peoplesmentioning
confidence: 99%
“…Historically, cancer disparities among FN Peoples have been implicitly and explicitly attributed to 'lifestyle deficits', including diet, physical activity, alcohol consumption, smoking, obesity and sexual behavior (Elias et al, 2011). More recently, these cancer disparities are understood as multifactorial, resulting from differences in access to care, negative healthcare experiences including discrimination and racism leading to delays in care, socioeconomic factors, and the ongoing impact of colonialism (Horrill et al, 2019b;McGahan et al, 2017;Withrow et al, 2017).…”
Section: Cancer Disparities Among First Nations Peoplesmentioning
confidence: 99%
“…Worldwide, Indigenous Peoples 1 have a higher cancer burden than non-Indigenous counterparts [1][2][3][4][5][6][7][8]. One report indicated that cancer incidence and mortality rates were higher in First Nations people in Canada for lung, colorectal, and kidney cancers as compared to non-First Nations people [2], while a comparison of 5-year survival and mortality rates for 15 cancers in a cohort population across Canada found that First Nations adults had poorer survival from all cancers except multiple myeloma, reaching over 20% lower for cervical and ovarian cancers and 10-15% lower for colorectal, breast, non-Hodgkin lymphoma, and leukemia [9].…”
Section: Introductionmentioning
confidence: 99%
“…One report indicated that cancer incidence and mortality rates were higher in First Nations people in Canada for lung, colorectal, and kidney cancers as compared to non-First Nations people [2], while a comparison of 5-year survival and mortality rates for 15 cancers in a cohort population across Canada found that First Nations adults had poorer survival from all cancers except multiple myeloma, reaching over 20% lower for cervical and ovarian cancers and 10-15% lower for colorectal, breast, non-Hodgkin lymphoma, and leukemia [9]. In the province of Manitoba, First Nations people diagnosed with cancer were significantly younger with significantly higher mortality rates, despite similar incidence rates after adjusting for age, sex, income, and area of residence [8]. The underlying causes of these disparities are wide ranging and complex, and include lower rates of screening and late-stage diagnoses [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes extend beyond Ontario, as data from 2004 to 2011 in the province of Manitoba reveal that First Nations (vs non-Indigenous Manitobans) were diagnosed with cancer significantly younger, had higher late-stage cancer diagnoses, and had higher mortality rates [ 6 ]. Further, First Nations in Manitoba living on reserve had higher proportions of late-stage diagnoses than First Nations living off reserve [ 7 ]. These findings suggest that cancer is an increasingly relevant health issue for Indigenous people in Canada, making optimal care for Indigenous cancer patients a significant concern to address.…”
Section: Introductionmentioning
confidence: 99%